Aged Caregivers in COVID-19: Geriatric Depression and Anxiety Prevalence Related to Psychosocial Characteristics - María Florencia Tartaglini; Silvina Lidia Heisecke; Paula Daniela Hermida; Carolina Feldberg; Silvia Deborah Ofman; María Verónica Somale; Diego Caruso (Liberabit, 2025)
Background: The COVID-19 pandemic affected aged familycaregivers’ access to support resources, increasing the burden ofcare due to psychological distress. Objective: To describe theprevalence of geriatric depression and anxiety in older adult familycaregivers during the COVID-19 pandemic and its association withpsychosocial characteristics. Method: Cross-sectional studyincluding 180 family caregivers replying to an onlinesociodemographic data questionnaire, GAD-7 and GDS-VE scales.Results: Caregivers’ median age was 66 years, 81% female, 71%employed, 57% parents or brothers/sisters and lived with therelative. The prevalence of geriatric depression and anxiety was46% and 71%, respectively. Anxiety levels were associated withcohabitation with the patient (OR 2.44). A trend between femalesex and the presence of anxiety (OR 2.41) was observed. Anassociation was also found between cohabitation with the patientand depression (OR 1.92). Cohabitation with the patientsignificantly increased the risk of depression (OR 2.22).Conclusions: Cohabitation with the patient was associated withdepression and onset of anxiety symptoms, remarkably in femalecaregivers.